Simultaneous nitrate and sulfide removal using a bio-electrochemical system - ÇALLI, BARIŞ (ELSEVIER SCIENCE SA, 2019)
This study addresses the applicability of simultaneous nitrate and sulfide removal using two-chamber bioelectrochemical systems (BES). The anode and cathode chambers of a BES were fed with the effluent of a sulfate reducing reactor and a nitrate-rich groundwater as an electron donor and acceptor sources, respectively. BES has been found to be effective for simultaneous removal of sulfide and nitrate coming from different sources and without mixing them. As a result, 10 gS/m(3)/d of sulfide oxidation and 7.26 gN/m(3)/d of nitrate reduction rates were achieved. The number of electrons used for denitrification was more than that of delivered from the anode, especially when the anode chamber was fed with the SRR effluent and operated at pH 7-7.5. It was supposed that H2S was used for denitrification in the cathode by passing through the membrane. Another reason for this might be the electrons released from the corroding steel mesh current collector. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Sulfide; Autotrophic denitrification; Bio-electrochemical systems; Groundwater; MICROBIAL FUEL-CELLS; ZERO-VALENT IRON; DENITRIFICATION; REDUCTION; RECOVERY; CARBON; WASTE